Data for the article The evolution of biomass-burning aerosol size distributions due to coagulation: dependence on fire and meteorological details and parameterization - Pierce, Jeffrey; Sakomoto, Kimiko (Colorado State University. Libraries, 2016)
This study calculated the evolution of aerosol size distributions in biomass burning plumes and is used the publication Sakamoto et al., 2016. In this repository we include the SAM-TOMAS input and output data that we used to build our emulator and simple fits. We also include the emulator code, which was also included in the supplementary material of our paper.
Department of Atmospheric Science